2021
DOI: 10.2147/oaem.s291648
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Risk Factors and Warning Signs of Stroke Among Patients with Heart Disease at Tikur Anbessa Specialized Hospital

Abstract: Background Stroke is a leading cause of mortality and disability worldwide and the economic costs of treatment and post-stroke care are extensive. The inability to identify stroke warning signs accurately is an important cause of delay in seeking medical attention, leading to potential ineligibility for acute intervention and which leads to secondary complications. Purpose To identify cardiac patients’ knowledge of stroke risk factors and warning signs. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
(27 reference statements)
3
14
0
Order By: Relevance
“…Hypertensive patients who had secondary education, and above were more than four times more likely to have adequate stroke knowledge. This was concordant with the findings of a range of studies in which high educational level had been the most associated factor with adequate knowledge of stroke in hypertensive patients in Ethiopia ( 26 , 28 , 29 ), and Nigeria ( 14 , 32 ) Morocco ( 25 ), and Beirut ( 33 ). This may be due to the fact that individuals who have a higher educational level may have more interaction with society and have easy access to health-related information from various sources like the internet, news, books, magazines, and literature as compared with individuals who have no formal education, which is supported by the systematic reviews reporting that educational status has a significant impact on cardiovascular disease knowledge in SSA populations ( 24 , 34 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hypertensive patients who had secondary education, and above were more than four times more likely to have adequate stroke knowledge. This was concordant with the findings of a range of studies in which high educational level had been the most associated factor with adequate knowledge of stroke in hypertensive patients in Ethiopia ( 26 , 28 , 29 ), and Nigeria ( 14 , 32 ) Morocco ( 25 ), and Beirut ( 33 ). This may be due to the fact that individuals who have a higher educational level may have more interaction with society and have easy access to health-related information from various sources like the internet, news, books, magazines, and literature as compared with individuals who have no formal education, which is supported by the systematic reviews reporting that educational status has a significant impact on cardiovascular disease knowledge in SSA populations ( 24 , 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…The data was collected using an interviewer-administered structured questionnaire adapted from previous literature ( 14 , 26 , 27 , 29 ), which contained socio-demographic, clinical, and lifestyle characteristics, stroke knowledge items, and stroke prevention practice items.…”
Section: Methodsmentioning
confidence: 99%
“…The adult emergency department (ED) of TASH had provided services to approximately 18,000 patients per year. The adult ICU of TASH had 16 surgical ICU beds and 16 medical ICU beds with a total of 32 adult intensive care unit beds [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Worldwide, former studies have shown poor knowledge of stroke symptoms and risk factors in the general public (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). According to studies conducted in Jordan (34), in Uganda (35), and in Egypt (29), 47, 75, and 68.2% of the subjects couldn't identify any stroke risk factor, respectively.…”
Section: Introductionmentioning
confidence: 99%